Molecular and Cellular Bases of Lipodystrophy Syndromes - Zammouri, Jamila; Vatier, Camille; Capel, Emilie; Auclair, Martine; Storey-London, Caroline; Bismuth, Elise; Mosbah, Héléna; Donadille, Bruno; Janmaat, Sonja; Fève, Bruno; Jéru, Isabelle; Vigouroux, Corinne (Frontiers in Endocrinology, 2022)
Lipodystrophy syndromes are rare diseases originating from a generalized or partial loss of adipose tissue. Adipose tissue dysfunction results from heterogeneous genetic or acquired causes, but leads to similar metabolic complications with insulin resistance, diabetes, hypertriglyceridemia, nonalcoholic fatty liver disease, dysfunctions of the gonadotropic axis and endocrine defects of adipose tissue with leptin and adiponectin deficiency. Diagnosis, based on clinical and metabolic investigations, and on genetic analyses, is of major importance to adapt medical care and genetic counseling. Molecular and cellular bases of these syndromes involve, among others, altered adipocyte differentiation, structure and/or regulation of the adipocyte lipid droplet, and/or premature cellular senescence. Lipodystrophy syndromes frequently present as systemic diseases with multi-tissue involvement. After an update on the main molecular bases and clinical forms of lipodystrophy, we will focus on topics that have recently emerged in the field. We will discuss the links between lipodystrophy and premature ageing and/or immuno-inflammatory aggressions of adipose tissue, as well as the relationships between lipomatosis and lipodystrophy. Finally, the indications of substitutive therapy with metreleptin, an analog of leptin, which is approved in Europe and USA, will be discussed.